THE EFFECT OF SOCIAL CAPITAL ON OPERATIONAL PERFORMANCE: RESEARCH IN BANKING SECTOR IN ERBIL - Hamad, Ahmed Abdulqader; Tuzlukaya, Şule; Kırkbeşoğlu, Erdem (Copernican Journal of Finance & Accounting, 2019)
Social capital as a field of study has grown with many contributions from different fields. Yet, the gap within the literature regarding different contexts has inspired researchers to look for further explanations about social capital and its dimensions. Therefore, this paper aims to provide insight into the impact of social capital as a specific factor to develop commercial banks’ operational performance in Erbil City, Iraq. To achieve this, a quantitative research is carried out, findings pointing to positive significant relationships between the dimensions of social capital as relational, structural and cognitive capital and operational performance development. Additionally, according to results, social capital plays a vital role in commercial banks’ stability and development of operational performance.